Insulin Edema Syndrome due to Rapid Glucose Correction in a Diabetic Patient - Siham M. Hussien; Hasan Imanli; Dena H. Tran; Robert D. Chow; Aseem Sood (Case Reports in Medicine)
Edema resulting from the initiation of insulin therapy or intensification of glycemic control is a rare and under-recognized complication. In this report, we present a case of a 46-year-old patient with insulin-dependent diabetes mellitus (IDDM) who avoided insulin treatment due to associated peripheral edema. Though rare, this phenomenon is typically seen in patients with elevated glucose levels who are initiated on insulin treatment, resulting in rapid correction and tight control of glucose levels. The diagnosis of insulin-induced edema is made after other causes of acute edema are ruled out. Furthermore, in this case report, we will also discuss the postulated mechanisms for the edema-causing property of insulin.